2019
DOI: 10.2196/13263
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the Use of Mobile Health in Improving Health Outcomes in Developing Countries: Systematic Review

Abstract: BackgroundThe use of mobile health (mHealth) technologies to improve population-level health outcomes around the world has surged in the last decade. Research supports the use of mHealth apps to improve health outcomes such as maternal and infant mortality, treatment adherence, immunization rates, and prevention of communicable diseases. However, developing countries face significant barriers to successfully implement, sustain, and expand mHealth initiatives to improve the health of vulnerable populations.Obje… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
205
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(216 citation statements)
references
References 50 publications
9
205
1
1
Order By: Relevance
“…Similarly, a recent systematic review of mHealth technologies in developing countries identified a lack of infrastructure and local equipment as a key barrier to scale-up of mHealth programs across multiple geographic locations [ 34 ]. As a result of our experiences, we would argue that if relevant local or regional design, manufacturing, and ICT support is routinely unavailable, this capacity should ideally be developed and nurtured to achieve the successful implementation of mHealth interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a recent systematic review of mHealth technologies in developing countries identified a lack of infrastructure and local equipment as a key barrier to scale-up of mHealth programs across multiple geographic locations [ 34 ]. As a result of our experiences, we would argue that if relevant local or regional design, manufacturing, and ICT support is routinely unavailable, this capacity should ideally be developed and nurtured to achieve the successful implementation of mHealth interventions.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of specificity for a given health condition could induce the perception of information overload [21], and some channels might be perceived as personal invasion [22]; these could be the reasons for the low willingness to be part of future programs in our study, particularly in the VMS arm. Previous reports have described other factors negatively associated with acceptability of SMS messages for health interventions in LMIC including lack of time (work conflict) [10] and psychosocial stressors such as caregiving roles and living in fear due to interpersonal violence and neighborhood insecurity [23].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a review found positive effects on healthy behaviors across age, minority status, and nationality [9]. However, several factors might influence effectiveness of mobile technology interventions including individual-associated factors (sociodemographics), technology-associated factors (platforms), and contextual factors [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…web GIS) and mobile devices or telemedicine (i.e. calls and short message services) (6) to reduce health costs (7), and improve health outcomes (8).…”
Section: Introductionmentioning
confidence: 99%